1995
DOI: 10.1002/tea.3660321008
|View full text |Cite
|
Sign up to set email alerts
|

Problems in Teaching the Topic of Redox Reactions: Actions and Conceptions of Chemistry Teachers

Abstract: Although there is growing interest in studies of teachers' actions and conceptions, little is known about content-related teaching problems arising in science classrooms. This article presents a case study of problems which can occur when teaching the topic of redox reactions to Grade 11 students. Two chemistry teachers, a senior and a junior teacher, were involved in the study. Their reflective comments on the teaching problems were also investigated. Research data were obtained from classroom observations an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
14

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 10 publications
3
56
0
14
Order By: Relevance
“…The results of the study above confirmed previous findings related to misconceptions (de Jong, 1982;de Jong et al, 1995;Nahum, Hofstein, Mamlok-Naaman, & Bar-Dove, 2004;Chiu, 2005;Barke, Hazari, & Yitbarek, 2009). The students' misconceptions were found on almost all chemistry topics, such as atomic structures, periodic systems, and chemical bonds (Redhana & Kirna, 2004).…”
Section: Table 2 Students' Misconception On Buffer Solution Materialssupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the study above confirmed previous findings related to misconceptions (de Jong, 1982;de Jong et al, 1995;Nahum, Hofstein, Mamlok-Naaman, & Bar-Dove, 2004;Chiu, 2005;Barke, Hazari, & Yitbarek, 2009). The students' misconceptions were found on almost all chemistry topics, such as atomic structures, periodic systems, and chemical bonds (Redhana & Kirna, 2004).…”
Section: Table 2 Students' Misconception On Buffer Solution Materialssupporting
confidence: 90%
“…The teacher-centered teaching that emphasizes the calculation aspects enables low comprehension and misconceptions among students. de Jong et al (1995) reported that, in fact, the chemistry teachers who taught redox reactions had a lot of learning problems related to the conceptual change model. These learning problems included they presented the unsuitable problems, presented the unnecessary explanations, explained the conceptions prematurely, used the confusing terms, taught the less context, ignored the alternative conceptions of students, discussed the less application of concepts (especially in industry), and explained too many procedures from experts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of studies report subject knowledge deficiencies among trainee teachers ('pre-service' teachers), for example in astronomy (Trumper, 2001); matter conservation (Haidar, 1997); chemical equilibrium (Quilez-Pardo & Solaz-Portoles, 1995), redox reactions (De Jong, Acampo, & Verdonk, 1995), and behaviour of gases (Lin, Cheng, & Lawrenz, 2000). It seems likely that teachers' own alternative conceptions themselves make up one significant factor in the development of some alternative conceptions among students, and so an important focus of the constructivist RP should be the characteristics of alternative conceptions which remain unchallenged by degree level study and initial teacher education courses, and may be actually presented as target knowledge in science teaching.…”
Section: Origins Of Alternative Conceptionsmentioning
confidence: 99%
“…As mentioned above, redox reactions are perceived to be one of the most difficult areas both to learn (de Jong and Treagust, 2002) and to teach (de Jong et al, 1995). Three important difficulties that students have are: 1) difficulties in comprehending oxidation and reduction as complementary reactions (de Jong and Treagust, 2002); 2) difficulties in identifying oxidizing and reducing agents (imprecise terminology and complex language use) (de Jong and Treagust, 2002); 3) the comprehension that a redox reaction is defined as a loss and a gain of oxygen (Garnett and Treagust, 1992;Schmidt 1997;Österlund and Ekborg, 2009).…”
Section: Learning and Redox Reactionsmentioning
confidence: 99%